Effects of secondary EGFR mutations on resistance against upfront osimertinib in cells with EGFR-activating mutations in vitro. (December 2018) - Nishino, Masaya; Suda, Kenichi; Kobayashi, Yoshihisa; Ohara, Shuta; Fujino, Toshio; Koga, Takamasa; Chiba, Masato; Shimoji, Masaki; Tomizawa, Kenji; Takemoto, Toshiki; Mitsudomi, Tetsuya
Highlights: Possible secondary resistant mutations against front-line osimertinib were examined. Together with Del 19, only C797S conferred significant resistance to osimertinib. Together with L858R, C797 and L718 mutations conferred resistance to osimertinib. TKI sensitivities depended on combinations of secondary and activating mutations. Abstract: Objectives: Non-small cell lung cancers (NSCLCs) that harbor activating mutations for epidermal growth factor receptor ( EGFR ) show remarkable initial response to EGFR-tyrosine kinase inhibitors (TKIs), but inevitably acquire resistance, half of which are due to a T790 M secondary mutation when first-generation (1 G) or 2 G EGFR-TKIs are used. Osimertinib, a 3 G EGFR-TKI, is a standard of care in this situation, but eventually also evokes resistance, reportedly due to some tertiary EGFR mutations. However, the FLAURA trial showed the superiority of osimertinib over 1 G EGFR-TKIs in treatment-naïve patients, thus providing an option of first-line osimertinib treatment. Resistance in this setting is also inevitable, but its mechanism is unclear. We investigated whether resistance mutations that emerged with T790 M were responsible for the osimertinib resistance in the first-line setting; i.e. without T790 M, and if so, what treatment option was available. Materials and Methods: We used literature search to identify EGFR mutations at codons L718, G724, L792, G796, and C797 as mechanisms of osimertinib resistance in the presence of T790 M. These mutations were introduced into Ba/F3 cells in cis with activating EGFR mutations but not with T790 M; inhibitory effects of five EGFR-TKIs were evaluated. Results: Only C797S conferred significant resistance against osimertinib when exon 19 deletion was the activating mutation. However, co-existence of L858R with C797S, C797 G, L718Q, or L718 V mutations all conferred resistance to osimertinib. Erlotinib showed the greatest activity for C797S-mediated resistance. However, 2 G EGFR-TKIs (afatinib or dacomitinib) were effective for other resistance mutations. Conclusion: After first-line osimertinib failure, 1 G or 2 G EGFR-TKIs are effective, depending on combinations of secondary and activating mutations.